Treasury of fairy tales : retold and illustrated - Biro, Val
This lavishly illustrated collection of enchanting fairy tales by the Brothers Grimm, Han Christian Andersen and Charles Perrault will delight children of all ages. Discover the magic of fairy tales with this enchanting treasury of best-loved stories. Ideal for sharing together, and to develop an enduring love of storytelling and reading, this collection with captivate any reader. This collection contains: - Little Red Riding Hood; The Ugly Duckling; Puss in Boots; Snow White and the Seven Dwarfs; The Emperor's New Clothes; Cinderella; The magic Porridge Pot.